Metabolic effects of dietary carbohydrates: The importance of food digestion - Giacco, Rosalba; Costabile, Giuseppina; Riccardi, Gabriele (Food research international, 2016)
High blood glucose and insulin concentrations, even if within the normal range, are associated with an increased risk to develop type 2 diabetes and cardiovascular diseases. Dietary carbohydrates are the main determinants of blood glucose levels in the postprandial period; therefore, the effects of dietary carbohydrates on human health are strongly related to their rate of digestion in the small intestine. This has raised much interest on food properties able to retard carbohydrate digestion and absorption. This review is focused to examine food properties which influence carbohydrate digestion in order to predict their potential influence on health markers. Among them, it is worth to underline the role of viscosity, the physical form of the food, cooking methods and processing, the type of starch (amylose or amylopectin), the presence of anti-nutrients and the amount of fiber, fat, and proteins. In this respect particularly relevant is the type of starch present in the food, since amylose is slowly digested by intestinal α-amylases while the digestion of amylopectin is faster. However, the food component that has the strongest impact on digestion and absorption of dietary carbohydrates is dietary fiber that modulates the postprandial glucose rise by multiple mechanisms. In fact, dietary fibers may increase ingesta viscosity, thus delaying the gastric emptying time and slowing both carbohydrate digestion and the rate of glucose transport to enterocytes. In addition, they can influence the composition of the gut microbiota and induce the production of short-chain fatty acids that beneficially affect glucose and lipid metabolism. In short, the knowledge of food characteristics able to retard carbohydrate digestion and absorption in the intestine can help modify food properties with the aim of improving their functionality. •Blood glucose level is a risk factor for cardiovascular diseases in healthy and diabetic subjects.•The rate of carbohydrate digestion in the intestine influences postprandial plasma glucose levels.•Type of starch, food structure, cooking and processing methods influence carbohydrate digestion.•Fibers may influence viscosity, gastric emptying rate, intestinal microbiota, and SCFAs production.•SCFAs modulate liver gluconeogenesis and lipogenesis by gene expression and hormone regulation.